2019
DOI: 10.1167/iovs.18-25880
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Optics Retinal Imaging inCNGA3-Associated Achromatopsia: Retinal Characterization, Interocular Symmetry, and Intrafamilial Variability

Abstract: Citation: Georgiou M, Litts KM, Kalitzeos A, et al. Adaptive optics retinal imaging in CNGA3-associated achromatopsia: retinal characterization, interocular symmetry, and intrafamilial variability. Invest Ophthalmol Vis Sci. 2019;60:383-396. https://doi.org/ 10.1167/iovs.18-25880 PURPOSE. To investigate retinal structure in subjects with CNGA3-associated achromatopsia and evaluate disease symmetry and intrafamilial variability.METHODS. Thirty-eight molecularly confirmed subjects underwent ocular examination, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 74 publications
7
69
1
1
Order By: Relevance
“…Foveal hypoplasia is a common feature in ACHM cohorts: all reported subjects with ATF6-ACHM, 23 and two thirds of the reported CNGA3-and CNGB3-ACHM subjects, have foveal hypoplasia. 10,22,28 In our cohort of GNAT2-ACHM, no case of foveal hypoplasia was observed, a finding similar to PDE6C-ACHM. 24 GNAT2 encodes guanine nucleotidebinding protein G(t) subunit alpha-2, which is part of the transducin complex, a G-protein participating in the visual cycle.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Foveal hypoplasia is a common feature in ACHM cohorts: all reported subjects with ATF6-ACHM, 23 and two thirds of the reported CNGA3-and CNGB3-ACHM subjects, have foveal hypoplasia. 10,22,28 In our cohort of GNAT2-ACHM, no case of foveal hypoplasia was observed, a finding similar to PDE6C-ACHM. 24 GNAT2 encodes guanine nucleotidebinding protein G(t) subunit alpha-2, which is part of the transducin complex, a G-protein participating in the visual cycle.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, in CNGA3and CNGB3-ACHM, peak cone density is severely reduced, with mean densities lower than the reported values for R1 (190 μm away from the fovea) in our cohort. 22,28 Scotoma on mesopic microperimetry was reported in all examined patients with GNAT2 (4/4), whereas only in 1 of 33 subjects examined with CNGA3-and CNGB3-ACHM. 10 In addition, BCVA, contrast sensitivity, reading acuity, and mean sensitivity were lower in the GNAT2 compared with the CNGA3 or CNGB3 groups.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…2,3 Main advantages of AO ophthalmoscopy include the ability to observe single cells in vivo and to track those same cells over time. Indeed, AO ophthalmoscopy has been used to describe the degeneration of cone photoreceptor structure using metrics, such as cone density or spacing, in numerous inherited retinal diseases, including retinitis pigmentosa, [4][5][6][7] Stargardt's, [8][9][10] achromatopsia, [11][12][13][14] and choroideremia (CHM), [15][16][17] among others. 2,3 In addition, investigators have demonstrated longitudinal imaging of the same photoreceptors over time.…”
Section: Introductionmentioning
confidence: 99%